2013
DOI: 10.1128/mcb.01744-12
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 Is Required for Formation of Senescence-Associated Heterochromatin Foci Induced by Oncogenic RAS or BRCA1 Loss

Abstract: bCellular senescence is an important tumor suppression mechanism. We have previously reported that both oncogene-induced dissociation of BRCA1 from chromatin and BRCA1 knockdown itself drive senescence by promoting formation of senescenceassociated heterochromatin foci (SAHF). However, the molecular mechanism by which BRCA1 regulates SAHF formation and senescence is unclear. BRG1 is a chromatin-remodeling factor that interacts with BRCA1 and pRB. Here we show that BRG1 is required for SAHF formation and senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…Previous studies indicated that β-galactosidase activity is a major characteristic found in senescence cells and is generally applied to senescence detection (65)(66)(67). In addition, many studies have reported that p16 and p21 protein levels are increased in senescence cells (50)(51)(52)(53). At present, a small fraction of RC-6-treated NT2 cells can express β-galactosidase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that β-galactosidase activity is a major characteristic found in senescence cells and is generally applied to senescence detection (65)(66)(67). In addition, many studies have reported that p16 and p21 protein levels are increased in senescence cells (50)(51)(52)(53). At present, a small fraction of RC-6-treated NT2 cells can express β-galactosidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RC-6 induced some cells to give rise to cellular senescence. Previous studies indicated that p16, p21 and p27 are related to cellular senescence in senescence cells (49)(50)(51)(52)(53). Therefore, these proteins were determined in the present study.…”
Section: Senescence Characteristics In Nt2 Cells After Rc-6 Treatmentmentioning
confidence: 99%
“…[14][15][16][17] The finding that loss of p16 rescues the functional decline of mammary stem cells and MEC senescence with Brca1 deficiency suggests that p16 blocks these cells from entering an active cell cycle. These results indicate that, in addition to the p53-p21 pathway that is activated by BRCA1 loss, [14][15][16] p16 is also a critical downstream target of BRCA1 in controlling mammary cell proliferation and senescence. In line with these data, it was recently reported in vitro that BRCA1 knockdown enhances the association of BRG1, a chromatinremodeling factor that interacts with BRCA1, with the p16 promoter, leading to activation of its transcription and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, it was recently reported in vitro that BRCA1 knockdown enhances the association of BRG1, a chromatinremodeling factor that interacts with BRCA1, with the p16 promoter, leading to activation of its transcription and senescence. 16 However, whether BRCA1 directly interacts with p16 promoter remains to be determined. More recently, it was found that human mammary epithelial cells from BRCA1-mutation carriers exhibit senescence, which is triggered by pRb pathway activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation